2009
DOI: 10.1007/s12257-008-0108-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biolinker on the detection of prostate specific antigen in an interferometry

Abstract: Prostate-specific antigen (PSA) has been identified as a significant biomarker for prostate cancer screening. Heavily-doped porous silicon, etched to form a Fabry-Perot fringe pattern, can be applied to an interferometric sensing for detecting PSA bound with PSA-antibody. In the previous works, a calyx crown derivative (Prolinker-A) was used as an alternative biolinker on the porous silicon surface for interferometric biosensing of DNA-damaging chemical instead of employing the conventional biomolecular affini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Prostate cancer is a major cancerous disease in the male population and accounts for about 10% of the deaths from cancers; [17][18][19] hence its early detection can save millions of lives. Monitoring the human Prostate-Specific Antigen (hPSA) level in serum is by far the most commonly used approach [19].…”
Section: Introductionmentioning
confidence: 99%
“…Prostate cancer is a major cancerous disease in the male population and accounts for about 10% of the deaths from cancers; [17][18][19] hence its early detection can save millions of lives. Monitoring the human Prostate-Specific Antigen (hPSA) level in serum is by far the most commonly used approach [19].…”
Section: Introductionmentioning
confidence: 99%
“…Although these elaborate antibody immobilization approaches can achieve relatively higher antigenbinding efficiencies, most of them need complicated molecular engineering or dedicated laboratory skills, making them limited for widespread, fast and costeffective applications [8]. The current industry prefers to use either direct printing or solution adsorption as efficient means for antibody immobilization.…”
Section: Introductionmentioning
confidence: 99%
“…Prostate cancer is a major cancerous disease in male population and accounts for about 10% of deaths from cancers. Its early detection can save millions of lives. Monitoring the prostate-specific antigen (PSA) level in serum is by far the most commonly used approach.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, quantitative detection of fPSA and PSA–ACT can effectively help diagnose prostate cancer. However, the low cutoff limit of the PSA (2.5–4 ng/mL) challenges current detection methods. , Techniques such as surface plasmon resonance (SPR), quartz crystal microbalance (QCM), electrochemical signal transduction, and microcantilever have all been explored for the detection of PSAs. , Many approaches including self-assembled monolayers (SAM), biotinylation, fluorescent labeling, protein linkers or ligands, nanoparticle conjugates, and secondary antibodies have been developed to improve detection sensitivity. ,, Among these different approaches, however, label-free detection methods are of interest for future biosensor applications. , We have recently demonstrated that neutron reflection (NR) is one of the techniques that can effectively determine antibody molecular orientations at the solid/water interfaces. ,, In this paper, spectroscopic ellipsometry (SE), NR, and dual polarization interferometry (DPI) have been combined to investigate the interfacial assembly of PSA antibody [mouse monoclonal anti-human prostate-specific antigen (anti-hPSA)] at the silicon oxide/water interface and the subsequent in situ antigen binding. The direct determination of in situ interfacial antibody orientation and its relationship to antigen binding is an important step in optimizing biosensor efficiency.…”
Section: Introductionmentioning
confidence: 99%